Дослідження динаміки вивільнення нестероїдного протизапального лікарського препарату амізону з полімерних лікарських форм пролонгованої дії - Рожнова, Р.А.; Галатенко, Н.А.; Замуліна, Л.І.; Нечаєва, Л.Ю.; Гладир, І.І. (Видавничий дім "Академперіодика" НАН України, 2007)
Studying the dynamic release of NSAID amizon from new polymeric medicinal forms on the base of segmented lactose-containing polyurethane elastomers is performed. It is shown that the intensity and the period of prolonged release of the drug depend on the nature of isocyanate, with which lactose was modified.